Cardiovascular effects of ozone in healthy subjects with and without deletion of glutathione-S-transferase M1 - Frampton, Mark W.; Pietropaoli, Anthony; Dentler, Michael; Chalupa, David; Little, Erika L.; Stewart, Judith; Frasier, Lauren; Oakes, David; Wiltshire, Jelani; Vora, Rathin; Utell, Mark J. (Inhalation toxicology, 2015)
Abstract Context: Exposure to ozone has acute respiratory effects, but few human clinical studies have evaluated cardiovascular effects. Objective: We hypothesized that ozone exposure alters pulmonary and systemic vascular function, and cardiac function, with more pronounced effects in subjects with impaired antioxidant defense from deletion of the glutathione-S-transferase M1 gene (GSTM1 null). Methods: Twenty-four young, healthy never-smoker subjects (12 GSTM1 null) inhaled filtered air, 100 ppb ozone and 200 ppb ozone for 3 h, with intermittent exercise, in a double-blind, randomized, crossover fashion. Exposures were separated by at least 2 weeks. Vital signs, spirometry, arterial and venous blood nitrite levels, impedance cardiography, peripheral arterial tonometry, estimation of pulmonary capillary blood volume (Vc), and blood microparticles and platelet activation were measured at baseline and during 4 h after each exposure. Results: Ozone inhalation decreased lung function immediately after exposure (mean ± standard error change in FEV1, air: −0.03 ± 0.04 L; 200 ppb ozone: −0.30 ± 0.07 L; p < 0.001). The immediate post-exposure increase in blood pressure, caused by the final 15-min exercise period, was blunted by 200 ppb ozone exposure (mean ± standard error change for air: 16.7 ± 2.6 mmHg; 100 ppb ozone: 14.5 ± 2.4 mmHg; 200 ppb ozone: 8.5 ± 2.5 mmHg; p = 0.02). We found no consistent effects of ozone on any other measure of cardiac or vascular function. All results were independent of the GSTM1 genotype. Conclusions: We did not find convincing evidence for early acute adverse cardiovascular consequences of ozone exposure in young healthy adults. The ozone-associated blunting of the blood pressure response to exercise is of unclear clinical significance.